Uridine as a new scavenger for synchrotron‐based structural biology techniques. (16th December 2016) - Crosas, Eva; Castellvi, Albert; Crespo, Isidro; Fulla, Daniel; Gil-Ortiz, Fernando; Fuertes, Gustavo; Kamma-Lorger, Christina S.; Malfois, Marc; Aranda, Miguel A. G.; Juanhuix, Jordi
Abstract : The protective properties of uridine against radiation damage for small‐angle X‐ray scattering and macromolecular crystallography experiments at room temperature are shown. The scavenging effect of uridine is similar to, or more pronounced than, the most commonly used scavengers. Abstract : Macromolecular crystallography (MX) and small‐angle X‐ray scattering (SAXS) studies on proteins at synchrotron light sources are commonly limited by the structural damage produced by the intense X‐ray beam. Several effects, such as aggregation in protein solutions and global and site‐specific damage in crystals, reduce the data quality or even introduce artefacts that can result in a biologically misguiding structure. One strategy to reduce these negative effects is the inclusion of an additive in the buffer solution to act as a free radical scavenger. Here the properties of uridine as a scavenger for both SAXS and MX experiments on lysozyme at room temperature are examined. In MX experiments, upon addition of uridine at 1  M, the critical dose D 1/2 is increased by a factor of ∼1.7, a value similar to that obtained in the presence of the most commonly used scavengers such as ascorbate and sodium nitrate. Other figures of merit to assess radiation damage show a similar trend. In SAXS experiments, the scavenging effect of 40 m M uridine is similar to that of 5% v/v glycerol, and greater than 2 m M DTT and 1 m M ascorbic acid. In all cases, the protective effect of uridine is proportional to its concentration.